Microphone Array Position Self-Calibration from Reverberant Speech Input - Jacob, Florian; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (International Workshop on Acoustic Signal Enhancement (IWAENC 2012))
In this paper we propose an approach to retrieve the geometry of an acoustic sensor network consisting of spatially distributed microphone arrays from unconstrained speech input. The calibration relies on Direction of Arrival (DoA) measurements which do not require a clock synchronization among the sensor nodes. The calibration problem is formulated as a cost function optimization task, which minimizes the squared differences between measured and predicted observations and additionally avoids the existence of minima that correspond to mirrored versions of the actual sensor orientations. Further, outlier measurements caused by reverberation are mitigated by a Random Sample Consensus (RANSAC) approach. The experimental results show a mean positioning error of at most 25 cm even in highly reverberant environments.
Keywords: Unsupervised; geometry calibration; microphone arrays; position self-calibration

Management und Marketing ferngesteuerter Dienstleistungen: Konzeptionelle Verortung, betriebswirtschaftliche Herausforderungen und künftige Forschungsaufgaben. - Wünderlich, Nancy; Schumann, Jan H; Wangenheim, Florian v; Holzmüller, Hartmut H (Zeitschrift für Betriebswirtschaft)
Die Möglichkeiten der Erbringung von Dienstleistungen haben sich durch die Entwicklungen der Informations- und Kommunikationstechnologien stark erweitert. Unter Zuhilfenahme moderner Formen der Datenfernübertragung kann eine breite Palette von Dienstleistungen technologisch vermittelt über große Entfernungen hinweg erbracht werden. Diesen als ferngesteuerte Dienstleistungen bezeichneten Angeboten kommt in der Praxis eine immer größere Bedeutung zu. In der betriebswirtschaftlichen Literatur wurde ihnen bisher jedoch wenig Beachtung geschenkt. In diesem Überblicksartikel erfolgt daher eine erste Auseinandersetzung mit betriebswirtschaftlich relevanten Aspekten ferngesteuerter Dienstleistungen. Ausgehend von einer begrifflichen Abgrenzung und Konzeptualisierung dieses neuen Dienstleistungstypus im Abgleich mit bestehenden Systematisierungsansätzen werden die spezifischen Herausforderungen des Management und Marketing von ferngesteuerten Dienstleistungen reflektiert und sowie künftige Forschungsaufgaben abgeleitet.
Keywords: Technologieintensive Dienstleistungen; remote services; Dienstleistungstechnologien

Intentionally positioned self-assembled InAs quantum dots in an electroluminescent p–i–n junction diode - Mehta, Minisha; Reuter, Dirk; Melnikov, Alexander; Wieck, Andreas D.; Michaelis de Vasconcellos, Steffen; Baumgarten, Tim; Zrenner, Artur; Meier, Cedrik (Physica E: Low-dimensional Systems and Nanostructures)
An intentional positioning of optically active quantum dots using site-selective growth by a combination of molecular beam epitaxy (MBE) and focused ion beam (FIB) implantation in an all-ultra-high-vacuum (UHV) setup has been successfully demonstrated. A square array of periodic holes on GaAs substrate was fabricated with FIB of 30 keV ions followed by an in situ annealing step. Subsequently, the patterned holes were overgrown with an optimized amount of InAs in order to achieve site-selective growth of the QDs on the patterned holes. Under well-optimized conditions, a selectivity of single quantum dot growth in the patterned holes of 52% was achieved. Thereafter, carrier injection and subsequent radiative recombination from the positioned InAs/GaAs self-assembled QDs was investigated by embedding the QDs in the intrinsic part of a GaAs-based p–i–n junction device. Electroluminescence spectra taken at 77 K show interband transitions up to the fifth excited state from the QDs.
Keywords: Molecular beam epitaxy; Focused ion beam; Self-assembled quantum dot; Electroluminescence

Guideline for the dependability-oriented design of self-optimizing systems - Sondermann-Wölke, Christoph; Hemsel, Tobias; Sextro, Walter; Gausemeier, Jürgen; Pook, Sebastian (Industrial Informatics (INDIN), 2010 8th IEEE International Conference on)
Self-optimizing systems are able to adapt their behavior autonomously according to their current self-determined objectives. Unforeseen influences could lead to dependability-critical behavior of the system. Methods are required which secure self-optimizing systems during operation. These methods to increase the dependability of the system should already be taken into consideration in the design process. This paper presents a guideline for the dependability-oriented design of self-optimizing systems, which integrates established classical methods like failure mode and effects analysis as well as methods based on self-optimization. On the one hand self-optimization is used to increase the dependability of the system by integrating objectives like safety, availability, and reliability to the objectives of the system. On the other hand methods are required to ensure the self-optimization itself. As basis for this guideline serves the principle solution of the system. The six phases of the guideline extend the design process and lead to an enhanced principle solution. Additionally, the guideline illustrates phases to implement and validate the self-optimizing system. The proposed guideline is applied to an innovative rail-bound vehicle, called RailCab, which is equipped with self-optimizing function modules.
Keywords: RailCab; dependability-critical behavior; dependability-oriented design; failure mode; rail-bound vehicle; secure self-optimizing systems; self-optimizing function modules; optimisation; railways; self-adjusting systems

Increasing the reliability of a self-optimizing railway guidance system - Sondermann-Wölke, Christoph; Geisler, Jens; Sextro, Walter (Reliability and Maintainability Symposium (RAMS), 2010 Proceedings - Annual)
Recent advances in information processing enable new kinds of technical systems, called self-optimizing systems. These systems are able to adapt their objectives and their behavior according to the current situation and influences autonomously. This behavior adaptation is non-deterministic and hence self-optimization is a risk to the system, e.g. if the result of the self-optimization process does not match the suddenly changed situation. In contrary, self-optimization could be used to increase the dependability by pursuing objectives like reliability and availability. In our preceding publications we introduced the so called multi-level dependability concept to cope with this new kind of systems (cf. [6]). This concept comprises the monitoring of the system behavior, the classification of the current situation, and the selection of the appropriate measure, if reliability limits are exceeded. In this paper we present for the first time experimental results. The dependability concept is implemented in the self-optimizing active guidance system of a railway vehicle. The test drives illustrate clearly that the proposed concept is able to cope with, e.g., sensor failures, and is able to increase the reliability and availability of the active guidance module.
Keywords: availability; dependability concept; multilevel dependability concept; railway vehicle; reliability; self optimizing active guidance system; self optimizing railway guidance system; situation classification; system behavior monitoring; optimal control; railways; reliability theory; self-adjusting systems

Probabilistic planning integrated in a multi-level dependability concept for mechatronic systems - Klöpper, Benjamin; Sondermann-Wölke, Christoph; Romaus, Christoph; Vöcking, Henner (Computational Intelligence in Control and Automation, 2009. CICA 2009. IEEE Symposium on)
Self-optimizing mechatronic systems are a new class of technical systems. On the one hand, new challenges regarding dependability arise from their additional complexity and adaptivity. On the other hand, their abilities enable new concepts and methods to improve the dependability of mechatronic systems. This paper introduces a multi-level dependability concept for self-optimizing mechatronic systems and shows how planning can be used to improve the availability and reliability of systems in the operating stages.
Keywords: multilevel dependability concept; probabilistic planning; self-optimizing mechatronic systems; systems reliability; mechatronics; planning (artificial intelligence); self-adjusting systems

Towards the Integration of Condition Monitoring in Self-Optimizing Function Modules - Sondermann-Wölke, Christoph; Sextro, Walter (Future Computing, Service Computation, Cognitive, Adaptive, Content, Patterns, 2009. COMPUTATIONWORLD '09. Computation World:)
New mechatronic systems, called self-optimizing systems, are able to adapt their behavior according to environmental, user and system specific influences. Self-optimizing systems are complex and due to their non-deterministic behavior comprise hidden risks, which cannot be foreseen in the design phase of the system. Therefore, this paper presents modifications of the current condition monitoring policy, to be able to cope with this new kind of systems. Beside avoiding critical situations evoked by self-optimization, the proposed concept uses self-optimization to increase the dependability of the system. In this case, the concept is applied to the active guidance module of an innovative rail-bound vehicle.
Keywords: condition monitoring; mechatronic systems; rail bound vehicle; rail guidance module; self-optimization; self-optimizing function modules; condition monitoring; mechatronics; railway rolling stock; self-adjusting systems

Development of a biomedical tissue differentiation system using piezoelectric actuators - Uribe, David Oliva; Stroop, Ralf; Hemsel, Tobias; Wallaschek, Jörg (Frequency Control Symposium, 2008 IEEE International)
In neurosurgery, delineation of tumor boundaries during resection of brain tumors is of substantial relevance. During operation distinction between tumor and healthy tissue rely on the abilities of the surgeon based on visual and tactile differentiation. In this paper a high sensitivity actuator-sensor system using a piezoelectric bimorph is presented. Frequency shift and transfer function of the bimorphpsilas voltages are detected and evaluated. Sensorpsilas sensitivity is evaluated using two frequency controls strategies: A phase-locked loop (PLL) and a self-oscillating circuit. Results of measurements conducted on gel-phantoms are presented and discussed.
Keywords: biomedical measurement; brain; cancer; neurophysiology; phantoms; phase locked loops; piezoelectric actuators; surgery; tactile sensors; transfer functions; tumours; PLL; biomedical tissue differentiation system; brain tumor resection; frequency control; frequency shift; gel-phantom; high sensitivity actuator-sensor system; neurosurgery; phase-locked loop; piezoelectric actuators; piezoelectric bimorph; self-oscillating circuit; sensor sensitivity; tactile differentiation; tactile sensor system; transfer function; tumor boundary; visual differentiation; Biomedical measurements; Circuits; Frequency control; Neoplasms; Neurosurgery; Phase locked loops; Piezoelectric actuators; Surges; Transfer functions; Voltage

Secure Profile Management in Smart Home Networks - Ziegler, Max; Müller, Wolfgang; Schäfer, Robbie; Loeser, Chris (Proceedings of the 1st International Workshop on Secure and Ubiquitous Networks (SUN-2005))
Currently, middleware for smart home networks with embedded and mobile devices are in the focus of several investigations. In this paper, we propose a middleware for secure management of device and user profiles by integrating a profile database with a generic authentication scheme for an X.509 enabled ticket management in the context of the OSGi framework. After the introduction of the individual system components and their interaction, we also discuss potential system attacks.
Keywords: Intelligent networks; Smart homes; Middleware; Project management; Data security; Ubiquitous computing; Context-aware services; Computer architecture; Home automation; Environmental management

Peer-To-Peer Technology for Interconnecting Web Services in Heterogeneous Networks - Schattkowsky, Tim; Loeser, Chris; Müller, Wolfgang (Proceedings of AINA2004)
The interconnection of software components is a key to enabling collaborative work. However, technology differences and security barriers like firewalls often hinder establishing collaborative infrastructures between enterprises or even within a single enterprise. We introduce a peer-to-peer based network infrastructure that transparently overcomes these problems using relay and routing mechanisms as well as different underlying transport protocols. We discuss the application of this technology to interconnect Web services.
Keywords: Peer to peer computing; Web services; Intelligent networks; Routing; Relays; Simple object access protocol; Collaborative work; Transport protocols; Network address translation; Java

Virtual Prototyping Of Self-Optimizing Mechatronic Systems - Gausemeier, Jürgen; Müller, Wolfgang; Paelke, Volker; Bauch, Jürgen; Shen, Q.; Radkowski, R. (Proceedings of the Design 2004)
Keywords: mechatronic systems; self-optimization; virtual prototyping